PENGARUH KOMPETENSI, KOMUNIKASI, DAN KEPERCAYAAN TERHADAP KERJA TIM (Studi di Inspektorat Kabupaten Tulungagung) - Arifin Arifin (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This research aimed to examine the effect of competence, communication, team work and trust in the case study in Inspektorat Kabupaten Tulungagung. Common problems in this research is work teams in Inspektorat Kabupaten Tulungagung. The population of this research is officers of Inspektorat Kabupaten Tulungagung who participate in regular inspection. The data is taken from questionnaires distributed to respondents. Variables in this research is competence, communication, trusted feeling and teamwork. Data were analyzed using multiple linear regression analysis. The results showed that the competence and communication no significant effect on teamwork, while the trusted feeling variables have a significant effect on teamwork. Implications of these findings for efforts teamwork optimal realization is the need for the provision of training to increase the competence and improved ways to communicate in team work Inspektorat Kabupaten Tulungagung officers